Educating producers on the profitability of precision agriculture technologies. (1st June 2017) - Shockley, J.; Mark, T.; Dillon, C.
Abstract : Producers are often faced with information from industry touting a generic return on investment of precision agriculture technologies that are inflated through the use of simple techniques that ignore the time value of money. The economics of precision technologies are as site-specific as the technology. Therefore, educating producers (and agribusiness) on how to determine the return on investment by following the correct investment analysis techniques within a proper decision-making framework helps ensure an accurate site-specific return on investment for precision agriculture technologies.